(untitled) (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2026)
Vocabulary instruction plays a crucial role in the development of communicative competence in young learners of English as a Foreign Language (EFL). However, traditional vocabulary teaching methods, such as rote memorization and isolated word drills, often fail to ensure meaningful learning and long-term retention among children. In response to this challenge, the stories method has emerged as an effective and learner-centered approach that integrates vocabulary learning into meaningful and engaging contexts. This article examines the effectiveness of the stories method in teaching vocabulary to young EFL learners, with particular emphasis on children aged 7–10 years. The study is grounded in cognitive, linguistic, and educational theories that highlight the importance of contextualized input, emotional engagement, and narrative structure in language learning. Stories provide rich linguistic input in which new vocabulary is embedded within coherent narratives, allowing learners to infer meaning naturally and retain lexical items more effectively. The article analyzes how storytelling supports vocabulary acquisition by activating prior knowledge, enhancing motivation, and facilitating deeper semantic processing. Special attention is given to the cognitive and psychological characteristics of young learners, such as imagination, developing memory, and sensitivity to meaningful input, which make storytelling especially suitable for this age group.